Quo Vadis Acehnese Shari’a: A Critical Approach to the Construction and Scope of Islamic Legislation - Danial Danial; Mahamatayuding Samah; Munawar Rizki Jailani (Al-Jami'ah: Journal of Islamic Studies, 2022)
The main purpose of implementing Shari’a is to benefit humanity in all areas of life in this worldly life and the hereafter. Based on this circumstance, this article critically sheds light on the existing implementation of Acehnese Shari’a by examining its scope and the existing qanun issued to seek that purpose. This article is grounded in a qualitative research query with a reflective approach. This study finds that the existing scope of the Acehnese Shari’a has not responded to the ideal of Shari`a, which is based on maqashid presumptions; dharuriyat, hajiah and tahsinat. The results of this study indicate that the application of Shari’a in Aceh is far from the goal of ideal Shari’a for its application does not cover every aspect of life, but is limited to only covers legal aspects (punishment). This study also shows that Acehnese Shari’a has not ruled over political affairs, governing system, health issues, economic matters, and defense issues. Therefore, the scope of Acehnese Shari`a implementation should be reconstructed in order to respond to the ideal  Shari’a, which is universal and inclusive.[Tujuan utama penerapan syariat Islam adalah untuk mencapai kemaslahatan umat manusia dalam segala bidang kehidupan di dunia dan di akhirat. Berdasarkan hal tersebut, artikel ini mencari peta implementasi penerapan syariat Islam di Aceh antara idealisme dengan realitas kekinian. Metode penelitian dalam artikel ini adalah penelitian kualitatif dengan pendekatan reflektif. Kajian ini mencerminkan cita-cita penerapan syariat Islam di Aceh dengan realitas yang terjadi, kemudian menyajikan roadmap agar syariat Islam dapat diterapkan di Aceh sesuai dengan ide dasarnya. Hasil penelitian ini menunjukan bahwa penerapan syariat Islam di Aceh jauh dari tujuan syariat Islam karena syariat Islam tidak muncul kecuali di bidang hukum (hukuman), dan juga kajian ini menunjukan bahwa  syariat  Islam di Aceh belum menyentuh permasalah politik, pemerintahan, kesehatan, ekonomi, pertahanan, pendidikan, sosial budaya, dan lingkungan, Oleh karena itu, peta implementasi harus direkonstruksi untuk menerapkan syariat Islam yang sesuai dengan cita-cita penerapan syariat Islam di Aceh]